Accessing Academic Library Services by Distance Learners - Owusu-Ansah, S.; Bubuama, C.K. (Library Philosophy and Practice, 2015)
This study seeks to investigate the accessibility of academic library services to distance learners, with specific reference to University of Ghana Library System (UGLS). A survey was conducted and one hundred and thirty eight (138) Level 400 distance learning students. The Statistical Package for Social Science (SPSS) is used to analyze the completed questionnaire. The results revealed that a greater proportion of the respondents were not aware of the library services because they were not available on the UGLS. Distance learners had no remote access to library electronic resources and other databases and therefore did not strongly agree to the provision of information needs through social media services. It was also evident that information needs of respondents were mostly not adequately provided for. The study recommended the following to the management of UGLS; awareness creation of library resources, user education on information literacy of library resources, encouraging the use of social media platforms, training/user education and initiation of borrowing of library resources.
Research Article
Keywords: Academic library services; distance learners; information needs; technology; accessibility